Gardenia jasminoides extract mitigates acetaminophen-induced liver damage in mice - Peenaprapa Tangpradubkiat; Maneerat Chayanupatkul; Pornpen Werawatganone; Kanjana Somanawat; Prasong Siriviriyakul; Naruemon Klaikeaw; Duangporn Werawatganon (BMC, 2024)
Abstract Background Acetaminophen (APAP)-induced hepatotoxicity is a potentially life-threatening condition. Gardenia jasminoides fruit extract (GJE), which contains geniposide (Gen) as its major active constituent, possesses anti-inflammatory and antioxidant properties and may help address the underlying pathogenesis of APAP-induced hepatotoxicity. This study aimed to evaluate the effects of GJE in a mouse model of APAP-induced hepatotoxicity. Methods Twenty-four male ICR mice were divided into 4 groups (n = 6/group): [1] Control group, mice were given distilled water; [2] APAP group, mice received a single dose of 600 mg/kg APAP; [3] APAP + low-dose GJE group, mice received APAP followed 30 min later by 2 doses of low-dose GJE (0.44 g/kg/dose, containing Gen 100 mg/kg/dose) 8 h apart; [4] APAP + high-dose GJE group, mice received APAP followed by 2 doses of high-dose GJE (0.88 g/kg/dose, containing Gen 200 mg/kg/dose). All mice were euthanized 24 h after APAP administration. Liver tissue was used for histological examination and to measure glutathione (GSH) and malondialdehyde (MDA) levels. Serum was used to determine levels of ALT and inflammatory cytokines (tumor necrosis factor- α (TNF-α) and interleukin-6 (IL-6)). Results Liver histopathology showed moderate to severe hepatic necroinflammation in the APAP group, whereas only mild necroinflammation was observed in both treatment groups. Serum ALT levels were significantly elevated in the APAP group compared to the control group but were significantly reduced after low- and high-dose GJE treatment. Serum TNF- α levels were significantly higher in the APAP group than in the control group and were significantly lower after high-dose GJE treatment (135.5 ± 477.2 vs. 35.5 ± 25.8 vs. 74.7 ± 47.2 vs. 41.4 ± 50.8 pg/mL, respectively). Serum IL-6 followed a similar pattern. Hepatic GSH levels were significantly lower in the APAP group compared to the control group but significantly increased after both low- and high-dose GJE treatment (19.9 ± 4.5 vs. 81.5 ± 12.4 vs. 71.4 ± 7.8 vs. 82.6 ± 6.6 nmol/mg protein, respectively). Conversely, hepatic MDA levels were significantly elevated in the APAP group compared with the control group but significantly decreased after high-dose GJE treatment (108.6 ± 201.5 vs. 40.5 ± 18.0 vs. 40.5 ± 16.8 nmol/mg protein, respectively). Conclusions Treatment with G. jasminoides fruit extract can alleviate APAP-induced hepatotoxicity, likely through its anti-inflammatory and antioxidant properties.